Prerequisites for Worldview Formation and the Main Stages of the Formation of a Life Path, Scientific-Pedagogical Activities of M. Darmanskyi - Olena Olytska (Pedagogical Discourse, 2022)
The article analizes the prerequisites for the formation of M. Darmanskyi’s worldview. In particular, it was established that the basis of M. Darmanskyi’s worldview and his subsequent professional orientation in the field of pedagogical activity constituted his parents. In addition, the environment, colleagues with whom M. Darmanskyi worked, also contributed to his professional and personal growth as a teacher, scientist, manager. The main essence of the stages of the life path, managerial and scientific-pedagogical activity of M. Darmanskyi is defined and revealed. The first stage – 1964–1975 – is the time of formation of scientific, philosophical and management views of M. Darmanskyi. The lower limit of the second stage of M. Darmanskyi’s activity (1975–1982) is caused by his transition to the position of director of secondary school № 13 in Kamianets-Podilskyi. The third stage of M. Darmanskyi’s managerial activity falls on his work as the head of the Kamianets-Podilskyi city department of public education (1980–1987). The fourth stage in M. Darmanskyi’s managerial activity is his appointment to the position of department head (head of department) of the Khmelnytskyi Regional Department of Public Education (1987–1992). The fifth stage in the activity of M. Darmanskyi is his work as the first deputy head of the Khmelnytskyi regional state administration (1992–1996), when his talent as a manager and citizen was fully manifested. The sixth stage of M. Darmanskyi’s managerial and scientific-pedagogical activity was work at the Khmelnytskyi Pedagogical School, which was later transformed into a humanitarian-pedagogical college, and then into the Khmelnytskyi Humanitarian-Pedagogical Institute (1996–2005).